The Role Tourism in achieving Economic Development in Iraq (1990 – 2015) - مسلم, حمدي شاكر; عبد الوهاب, نور عبد الرزاق (Journal of Economics and Administrative Sciences, 2018)
Abstract       Tourism is one of the essential economic fields of many countries, both developed and developing. The social plays a greater role in the continuous awareness of a tourist culture based on the need to attract tourists continuously. the tourism heritage and state-owned tourism are the main factors in attracting more tourists. The interest in this strategic sector makes the country the first and most active framework in the development of appropriate mechanisms for investment in this sector, all within the framework of sustainable development of society through the rational use of resources obtained by various bodies in the implementation of several development projects whose capital is the return on the funds obtained is the effect of efficiency in the tourism sector .Tourism has become one of the leading industries that generate a large income and has been relied on in many countries such as Egypt, Tunisia, Morocco ,Italy ,Malaysia…ext. and which have succeeded in increasing its resources and described tourism as the new economic giant and the most developed industry because the industry plays an important role in the economic development of the country. a source of income in foreign currency and the creation of employment opportunities in addition to its role in the promotion of investment and the development and development of tourist areas.nd development of tourist areas.